Strategi Peningkatan Jumlah Nasabah pada Produk Pembiayaan Gadai Emas di PT Pegadaian UPC Hang Tuah Duri - Nancy Qonitha; Mariatul Fitri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study examines the problem of the low growth in the number of customers for gold pawn financing products at PT Pegadaian UPC Hang Tuah Duri, influenced by suboptimal marketing strategies, low financial literacy among the community, and competition from other financial institutions. The aim of this research is to analyze strategies for increasing the number of customers through social approaches, service improvement, and building public trust. The method used is a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation involving employees and customers of Pegadaian. The results show that customer growth strategies are implemented through strengthening socio-religious communication, improving service quality, community-based promotion, and utilization of digital media. In addition, customer trust is a key factor in encouraging product usage decisions. The implementation of these strategies has gradually and sustainably increased public interest in becoming customers within the local financial service market context in Indonesia.